2007
DOI: 10.1038/sj.ki.5002103
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of complement factor C5 protects against anti-myeloperoxidase antibody-mediated glomerulonephritis in mice

Abstract: In mice, administration of murine anti-myeloperoxidase (MPO) IgG induces pauci-immune necrotizing crescentic glomerulonephritis. Recent studies in this model indicate a crucial role for complement activation in disease induction. Here, we investigated the effect of pretreatment or intervention with a C5-inhibiting monoclonal antibody (BB5.1) in the mouse model of anti-MPO IgG-induced glomerulonephritis. Mice received BB5.1 8 h before or 1 day after disease induction with anti-MPO IgG and lipopolysaccharide. Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
169
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(175 citation statements)
references
References 36 publications
(36 reference statements)
1
169
1
4
Order By: Relevance
“…Second, the complement system might be another potential contributor. Although AAV has traditionally been characterized as pauci-immune, and decreased levels of circulating C3 are uncommon in AAV, recent studies have demonstrated that activation of the alternative complement pathway plays a critical role in the pathogenesis of AAV (26)(27)(28)(29)(30). Patients with active AAV have elevated levels of circulating C3a, C5a, soluble C5b-9, and Bb, which suggests activation of the complement system via the alternative pathway (30).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the complement system might be another potential contributor. Although AAV has traditionally been characterized as pauci-immune, and decreased levels of circulating C3 are uncommon in AAV, recent studies have demonstrated that activation of the alternative complement pathway plays a critical role in the pathogenesis of AAV (26)(27)(28)(29)(30). Patients with active AAV have elevated levels of circulating C3a, C5a, soluble C5b-9, and Bb, which suggests activation of the complement system via the alternative pathway (30).…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis that complement activation is important after 24 hours is supported by the finding that complement inhibition in the same model via intervention with a C5-inhibiting mAb after 24 hours attenuates disease progression, illustrated by a decrease in urinary abnormalities and a strong reduction in glomerular crescent formation. 26 A limitation of the mouse model of anti-MPO IgG/LPSinduced NCGN is that disease is induced by the passive, onetime transfer of anti-MPO IgG, which results in a rapid, monophasic renal disease. This is clearly different from ANCA-associated glomerulonephritis in humans, whereby ongoing disease activity results in the progressive accumulation of new lesions.…”
Section: Days (ⅺ) Mice That Received Deglycosylated Anti-mpo Igg () mentioning
confidence: 99%
“…Periodic acid-Schiff staining was performed on paraffin sections, and the number of glomerular crescents was counted in 100 consecutive glomerular cross-sections in a blinded manner, as described previously. 26 Immunohistochemical staining for neutrophils was performed on acetone-fixed 5-m cryosections using an anti-rabbit peroxidase-based Envisionϩ system (DakoCytomation, Carpinteria, CA) according to the manufacturer's protocol. Sections were incubated for 30 minutes with 10 g/ml rat antimouse-Ly6G (clone 1A8; BD Biosciences, Breda, Netherlands) or isotype control antibody (IgG2a; Antigenix America, Huntington Station, NY) followed by a 30-minute incubation with 10 g/ml unlabeled rabbit anti-rat secondary antibody (Vector Laboratories, Burlingame, CA).…”
Section: Production Of Polyclonal Mouse Anti-mpo Iggmentioning
confidence: 99%
“…With use of these model systems, TNF␣, complement, chemokines, and integrins were identified as potential targets. [22][23][24][25][26] We optimized an MPO-ANCA mouse model and showed that the complement receptor C5a and the PI3K␥ isoform are novel targets. 27,28 We used this model to assess NCGN with the 26S proteasome inhibitor bortezomib (BTZ), compared with standard steroid/cyclophosphamide (S/CYC) treatment.…”
mentioning
confidence: 99%